Bulgaria : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper investigates the role of debt overhang in explaining weak nonfinancial corporate (NFC) investment in Bulgaria using firm-level data. The study confirms a negative association between measures of debt overhang and investment for Bulgarian NFCs using firm-level data. Bulgaria's NFCs are the most leveraged among new member states. The findings suggest that high NFC debt overhang could be an important drag on investment. While credit demand is likely to pick up in line with economic activity, high NFC indebtedness could continue to stand in the way of corporate credit recovery. A possible direction for future work is to investigate the existence of different investment cycles across business activities/sectors, and their role in explaining the identified negative relationship. Policies that help reduce the corporate debt overhang could help boost credit and growth. Policy initiatives such as an efficient corporate debt restructuring framework and tax measures could help corporate deleveraging. The findings suggest that high corporate debt could be an important drag on investment.